Trace metal fate in soil after application of digestate originating from the anaerobic digestion of non-source-separated organic fraction of municipal solid waste - Baldasso, Veronica; Bonet-Garcia, Neus; Sayen, Stéphanie; Guillon, Emmanuel; Frunzo, Luigi; Gomes, Carlos A. R.; Alves, Maria João; Castro, Ricardo; Mucha, Ana Paula; Almeida, C. Marisa R. (Frontiers in Environmental Science, 2023)
Digestate originating from anaerobic digestion of non-source-separated organic fraction of municipal solid waste (OFMSW) is produced abundantly worldwide and generally discarded in landfills. However, it can be a valuable resource for many bioeconomy strategies as land restoration, only if a consolidated understanding of the contaminants’ presence and behaviour in digestate-amended soil is achieved. This study aimed to investigate the fate of trace metals, namely Zn, Cu, Pb, and Cr found in the digestate, along the soil profile after digestate application on soil, and the influence that other contaminants as pharmaceutical compounds can have on their behaviour in the soil system. For that, a 90-day soil column experiment was conducted using a fine loamy sand soil topped with a layer of digestate-amended soil. Digestate-amended soil had a soil to digestate proportion of 14 to 1 (dry weight). Two experimental conditions were tested: soil amended with digestate, and soil amended with digestate spiked with the antidiabetic drug metformin. Soil samples were taken at 4 depths on days 1, 7, 21, 35 and 90, and total trace metals concentrations and fractionation was determined via atomic absorption spectroscopy. Results showed that Zn, Cu, Pb ad Cr initially present in the digestate were transferred from the digestate-amended soil layer to the underlying soil layer over time, although in low amounts. Nevertheless, no transfer was detected to the deeper soil layers. Trace metals in soil were predominantly in immobile and less bioavailable forms associated with clay and silicate mineral groups, whereas in the digestate-amended soil they were in more bioavailable forms, which could be related also to metals’ migration in the soil layers below. Results also show that the presence of metformin had no influence on trace metal behaviour, giving insight also on possible interactions with other potentially present contaminants as microplastics. The current study showed that OFMSW digestate can be a promising organic nutrient-rich matrix for land restoration even if it may contain high metals’ concentrations because low metal mobility along the soil profile can be expected.